A Review of Key Technologies and Properties for Graphene Cu-Based Composites. Issue 1 (August 2021) - Liu, K M; He, G Y; Sheng, X C; Han, N L; Li, M L; Zhang, M C; Zou, J; Fu, K; Huang, H M
Abstract: Cu-based composites are widely used in mechanical, electrical, communication, transportation and microelectronics industries due to their excellent properties. However, the difficult match between strength and conductivity is the main problem for Cu-based composites. And thermal-mechanical treatment technologies reached the limit to improve and control their comprehensive performance. Graphene is a two-dimensional layered material with carbon atoms hybridized by SP2 orbital, and has high strength, good electrical conductivity and thermal conductivity. It is expected to solve the contradiction between the strength and conductivity of the composites by introducing graphene into Cu-based composites. In this paper, the commonly used methods for effective dispersion of graphene and interface bonding were introduced, the researches on the strength, toughness, electrical conductivity and thermal conductivity were outlined, lastly the future development of graphene Cu-based composites was prospected.